Effects of Concurrent Training on Oxidative Stress and Insulin Resistance in Obese Individuals - Medeiros, Niara da Silva (Oxid Med Cell Longev, 2015)
Obesity is associated with insulin resistance (IR) and increased oxidative stress. Thus, the present study aimed to evaluate anthropometric parameters, IR, and oxidative stress in obese individuals subjected to two types of concurrent training at the same intensity but differing in frequency. Accordingly, 25 individuals were divided into two groups: concurrent training 1 (CT1) (5 d/wk) and concurrent training 2 (CT2) (3 d/wk), both with moderate intensity. Anthropometric parameters, IR, and oxidative stress were analyzed before and after 26 sessions of training. Both groups had reduced body weight and body mass index (P < 0.05), but only CT1 showed lower body fat percentage and increased basal metabolic rate (P < 0.05). Moreover, CT1 had increased HOMA-IR and decreased protein damage (carbonyl level), and CT2 had decreased HOMA-IR and increased lipid peroxidation (TBARS level) (P < 0.05). On the other hand, both training protocols reduced the GPx activity. It can be concluded that both types of concurrent training could be an alternative for lowering body weight and BMI. Also, it was observed that concurrent training, depending on the frequency, can contribute to reducing body fat, oxidative damage (protein oxidation), and IR but can induce oxidative damage to lipids. More studies are needed to elucidate the mechanisms involved.